Anti-endotoxin and anti-inflammatory effects of Chinese herbal medicinal alkaloid ingredients in vivo. (October 2016) - Hu, Yiyi; Mao, Aihua; Yu, Zhengyu; He, Kongwang
Abstract: The aim of the research was to investigate the anti-endotoxin and anti-inflammatory effects of sinomenine, fangchinoline, stachydrine, chuanxionggzine, oxymartrine, and evodiamine alkaloids commonly found in Chinese herbal medicines. In an endotoxin (LPS) control group, each mouse was challenged with 1 mg LPS/kg by intraperitoneal (IP) injection. In high-, middle- and low-dose alkaloid groups, mice were initially challenged with 1 mg LPS/kg by IP injection and, 3 h later, dosed intramuscularly (IM) with one of the six alkaloids at one of three levels (1, 5, or 10 mg/kg body weight). In the drug control group, mice were dosed IM with 10 mg/kg body weight of a given alkaloid; mice in a naïve control group were administered the same volume of normal saline. The results revealed the six alkaloids could reduce the incidence/severity of LPS- induced toxicities, e.g., body temperature elevation, weight loss, systemic inflammation, multiple organ dysfunction. Taken together, the data suggested to us that these alkaloids might effectively regulate inflammatory responses and have a potential to be used in anti-endotoxin therapies. Highlights: Investigate anti-inflammatory effect of sinomenine, fangchinoline, stachydrine, chuanxionggzine, oxymartrine and evodiamine. Six alkaloids could reduce the incidence/severity of LPS- induced toxicities. These alkaloids might effectively regulate inflammatory responses and have a potential used in anti-endotoxin therapies.